Rules Based Algorithm for AI game JADDWAL - Karim, Hafiz Al; Olow, Ali Muhammud; Afifah, Muthiah (Universitas Gajah Putih, 2022)
The video game landscape is populated by games that rely on AI to make the player have a challenging and enjoyable experience, especially as games keep getting better and better in terms of performance and technology, soon it will be hard to ignore it as just a game and perceive it as a technological accomplishment, In this paper, we implemented a Rules-Based Algorithm to create an AI for a relatively simple game, We further analyze how the AI works and functions and if it would be the best suited for a simple video board game. :